Avaliação da ação da quitosana em orabase na reparação tecidual quando associada ou não ao laser visível de λ 660 NM - Gurgel, Ricardo Alexandre Soares (2010)
The present work was developed as objective to evaluate macrocospically and morphologically the effect of the chitosan in orabase, associated or not to the 660 nm laser in the tissue repair. In this experimental study were used 75 rats, male, of the Wistar strain, randomly divided into 5 groups: G1 (control), G2 (orabase), G3 (orabase of chitosan 2%), G4 (laser) and G5 (laser + orabase of chitosan 2%). They had been confectioned wounded in the back of the animals measuring around 5 mm and had been obeyed to the periods of observation and sacrifice with 3, 7 and 14. The results were subjected to statistical analysis. From the results can be concluded that in the initial period of healing, the use of chitosan in orabase associated laser promoted, macroscopically, greater contraction of the wound and better standards of healing. The group treated with chitosan showed similar results, as the group treated with Laser, about the control of inflammation, formation of crust and angiogenesis, in addition to promoting greater early in reepithelialization. Treatment with chitosan in orabase showed levels of collagen similar to the laser.